2015
DOI: 10.1017/s0950268815000278
|View full text |Cite
|
Sign up to set email alerts
|

IFITM3 rs12252 T>C polymorphism is associated with the risk of severe influenza: a meta-analysis

Abstract: The interferon-inducible transmembrane protein 3 (IFITM3), as one of the key genes involved in the interferon pathway, is critical for defending the host against influenza virus, and the rs12252 T>C variant in IFITM3 might be associated with susceptibility to severe influenza. Owing to contradictory and inconclusive results, we performed a meta-analysis to assess the association between rs12252 T>C polymorphism and severe influenza risk. A comprehensive literature search up to 1 August 2014 was conducted in EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…The only alterations in a gene associated with severe seasonal influenza in hospitalized patients were two single nucleotide polymorphisms (SNP) in IFITM3. One, rs12252, leads to a truncation (Everitt et al 2012;Xuan et al 2015;Zhang et al 2013), and the other, rs34481144i, to diminished expression and impaired recruitment of immune CD8+ T cells into the infected airways (Allen et al 2017). Still, the role of IFITM3 in human influenza infections remains controversial (Mills et al 2014;Williams et al 2014;Zani and Yount 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The only alterations in a gene associated with severe seasonal influenza in hospitalized patients were two single nucleotide polymorphisms (SNP) in IFITM3. One, rs12252, leads to a truncation (Everitt et al 2012;Xuan et al 2015;Zhang et al 2013), and the other, rs34481144i, to diminished expression and impaired recruitment of immune CD8+ T cells into the infected airways (Allen et al 2017). Still, the role of IFITM3 in human influenza infections remains controversial (Mills et al 2014;Williams et al 2014;Zani and Yount 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Host genes associated with severe influenza virus in humans with severe IAV-H1H1 and IAV-H7N9 disease in some, but not all, cohorts(135)(136)(137)(138)(139)(140)(141)(142)(143)(144). rs34481144 was associated with reduced gene expression in CD8 + T cells and severe IAV disease(110).…”
mentioning
confidence: 99%
“…However, for individuals with mild infection, no significant association was observed. These findings suggested that the rs12252T>C SNP is significantly correlated with an increased risk of severe influenza but not with the likelihood of early influenza infection [12] . The discrepancy between the results of Mills et al [10] and meta-analysis data may be due to differences in sample sizes, statistical power, and ethnic groups.…”
Section: Introductionmentioning
confidence: 92%